The Indigenous Aetas of Bataan, Philippines: Extraordinary Genetic Origins, Modern History and Land Rights - McHenry, M.; Anwar McHenry, Julia; Balilla, V.; Parkinson, R.M. (Blackwell Publishing Asia, 2013)
The Aeta Magbukún of Bataan in Luzon, the Philippines remain one of the least known and documented Indigenous tribes. They retain primarily subsistence hunter-gathering strategies to supply their basic needs. They also strive for recognition of their ancestral connection with, and rights to inhabit their ancestral forest domains, which is threatened by the expansion of agriculture and urban development by non-Aetas, primarily the majority Tagalog population. The Aeta continue to endure dispossession, poverty and political discrimination through decades of protracted land rights processes. This review explores the potential use of recent genetic evidence in anthropology and human geography to legitimize the Aeta’s status as Indigenous people and contradict the perspective of some governments in the Asia Pacific region who question the existence of Indigenous peoples generally, often from fear of land tenure and associated political repercussions. The acquisition and use of genetic research on Indigenous populations is both socially and politically contested through fear of the potential to jeopardize sovereignty claims and lead to biologically-based discrimination. However, the full implications of the potential use of genetic research to legitimize Indigenous status, as described within this research, has yet to be thoroughly explored. By exploring both the genetic and anthropological evidence using a case study of the Indigenous Aeta, this paper provides a unique approach to building a case for Indigenous rights, occupation, use of ancestral lands, self-determination, and ultimately, recognition as Indigenous people.